The structure of Synechococcus elongatus enolase reveals key aspects of phosphoenolpyruvate binding - Gonzalez, Javier Marcelo (2022)
A structure-function characterization of Synechococcus elongatus enolase (SeEN) is presented, representing the first structural report on a cyanobacterial enolase. X-ray crystal structures of SeEN in its apoenzyme form and in complex with phosphoenolpyruvate are reported at 2.05 and 2.30 Å resolution, respectively. SeEN displays the typical fold of enolases, with a conformationally flexible loop that closes the active site upon substrate binding, assisted by two metal ions that stabilize the negatively charged groups. The enzyme exhibits a catalytic efficiency of 1.2 × 105 M -1s-1for the dehydration of 2-phospho-d-glycerate, which is comparable to the kinetic parameters of related enzymes. These results expand the understanding of the biophysical features of these enzymes, broadening the toolbox for metabolic engineering applications.